Beckett's Dedalus : Dialogical Engagements with Joyce in Beckett's Fiction - Murphy, P. J. (Peter John), 1946- (Book collections on Project MUSE., 2009)
Paying close attention to the extensive network of allusions Beckett derived from Joyce's writing, P.J. Murphy reveals how Beckett consistently echoed and engaged in dialogue with Joyce's works.